A Critical Companion to Zoosemiotics: People, Paths, Ideas - Martinelli, Dario; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
A Critical Companion to Zoosemiotics is the first attempt to systematize the discipline that studies animal communication and signification through its most important and/or problematic terms and concepts, and its most representative scholars. It is a companion, in that it attempts to cover the entire range of key words of the field, and it is critical, in that it aims not only to describe, but also to discuss and problematize such words. The book is conceived for zoosemiotic students, researchers and scholars as a valuable tool for consultation, reference, research and reflection, and it represents an ideal complement for reading and studying zoosemiotic books and essays.
Keywords: Life sciences; Animal behavior; Forests and forestry; Life Sciences; Behavioural Sciences; Forestry